HUBUNGAN AKTIVITAS MENGGAMBAR MENGGUNAKAN TEKNIK KERING DENGAN PERKEMBANGAN MOTORIK HALUS ANAK USIA DINI - Nuri Imani (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
This study aims to determine the reality of drawing activities using dry techniques, the reality of the fine motoric development of early childhood, and the reality of the relationship between drawing activities using dry techniques and the fine motoric development of children aged in group B RA Nurul Hikmah Kertasari Garut. Quantitative correlation is one of the methods used in this research. Children of group B RA Nurul Hikmah Kertasari Garut are the subjects of this study, totaling 15 children in the 2020/20201 period. Observation, performance, and documentation are data collection techniques in this study. The value of the calculation results on variable X obtained an average value of 70. This value is in a good category because it is in the interval 66-79. Meanwhile, the Y variable obtained an average value of 71. The value is included in the good category where it is in the interval 66-79. The relationship between drawing activities using dry techniques and fine motor development of early childhood children in group B RA Nurul Hikmah Kertasari Garut has a correlation coefficient of 0.47. This figure is in the interval 0.4000-1000 so it is included in the strong category. The result of the value from the significance is known as tcount> ttable (1.92 <1.93), the price of ttable = 1.93, it can be translated that is accepted, thus there is a significant relationship between the activity of drawing using dry techniques and the development of fine motor skills in early childhood.